A 2012 Social Accounting Matrix (SAM) for South Africa - Dirk van Seventer; Faaiqa Hartley; Sherwin Gabriel; Robert H. Davies (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper documents the construction of a South African Social Accounting Matrix (SAM) for the year 2012. The SAM is built using a Statistics South Africa Supply Table and Use Table, National Accounts, and various household and labour market surveys. It provides a detailed representation of the South African economy and identifies 62 activities and 104 commodities; labour is disaggregated by education attainment level; and households by per capita expenditure deciles. Information on labour is drawn from the 2012 Labour Market Dynamics Survey of the Quarterly Labour Force Survey. Data on households is taken from the 2008/9 Living Conditions Survey. The SAM identifies government, investment, and foreign accounts. It is a useful database for conducting economy-wide impact assessments, including SAM-based multiplier analysis and computable general equilibrium modelling.
Keywords: 330; social accounting matrix; national accounts; supply table; use table; cross-entropy SAM estimation